Reproductive capital: theoretical foundations and empirical evidence from the workplace - Hadley, Robin A.; Mumford, Clare; Carroll, Michael; Wilkinson, Krystal (Frontiers in Sociology, 2025)
IntroductionThe workplace encompasses structural and personal tensions related to both reproduction and non-reproduction, as well as ambiguity and ambivalence permeate policies, practices, and social interactions. The aim of this study was to explore and record participants' diverse fertility journeys and the effect of work on their preconception/infertility experience.MethodThe concept of “reproductive capital” emerged from a latent thematic analysis of semi-structured bio-narrative interviews with 80 people (67 women and 13 men) and their accounts of how the workplace affected their reproductive journeys.ResultsThe workplace was an alienating space for people accessing Assisted Reproductive Technology (ART) treatment, who were subjected to scrutiny and judgment. The challenges faced by individuals included matters surrounding disclosure and subsequent consequences, desired/expected support, and what was received. Some participants challenged the pronatalist policy status quo and sought change to make the workplace more inclusive. Participants' accounts highlighted numerous situations in which reproductive capital was present.DiscussionContextualizing theory through empirical data allows for a broader understanding of how socio-economic, socio-cultural, norms, and values influence individual and organizational behavior. This article critically examines the concept of “reproductive capital” and its interaction with other forms of capital: aging, biological, cultural, economic, social, and symbolic.